2022
DOI: 10.31083/j.fbl2712321
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Role of SGLT2 Inhibition with Dapagliflozin in the Development of Diabetic Retinopathy

Abstract: Background: Diabetic retinopathy (DR) is a major cause of blindness globally. Sodium Glucose Cotransporter-2 (SGLT2) inhibitors have been demonstrated to exert cardiorenal protection in patients with diabetes. However, their potential beneficial effect on DR is less well studied. The aim of the present study was to determine the effects of the SGLT2 inhibition with Dapagliflozin (DAPA) on DR in well-characterised DR mouse models and controls. Methods: Dapagliflozin was administered to mice with and without dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…revealed that empagliflozin reduced retinal vascular leakage and suppressed the expression of pathogenic vascular endothelial growth factor in the retina using a relevant mouse model (Akimba) of type 1 diabetes mellitus 16 . They also found that dapagliflozin attenuated retinal microvascular and neural abnormalities while concurrently augmenting the expression of fibroblast growth factor 21 17 . Notably, they had a novel observation that SGLT2 inhibition leads to the upregulation of SGLT1 protein in the retina.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…revealed that empagliflozin reduced retinal vascular leakage and suppressed the expression of pathogenic vascular endothelial growth factor in the retina using a relevant mouse model (Akimba) of type 1 diabetes mellitus 16 . They also found that dapagliflozin attenuated retinal microvascular and neural abnormalities while concurrently augmenting the expression of fibroblast growth factor 21 17 . Notably, they had a novel observation that SGLT2 inhibition leads to the upregulation of SGLT1 protein in the retina.…”
Section: Discussionmentioning
confidence: 98%
“…16 They also found that dapagliflozin attenuated retinal microvascular and neural abnormalities while concurrently augmenting the expression of fibroblast growth factor 21. 17 Notably, they had a novel observation that SGLT2 inhibition leads to the upregulation of SGLT1 protein in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that SGLT2i’s may be a potential therapeutic for not just T2D but also T1D. When our Akimba mice were treated with the SGLT2i’s DAPA [ 85 ], CANA [ 86 ] and EMPA [ 86 ], metabolic parameters such as fasting blood glucose levels, polydipsia (excessive thirst) and weight management were all improved. Aside from the metabolic advantages in our T1D mice, we determined that DAPA and EMPA conferred beneficial effects on (i) digestive health [ 42 ] by significantly increasing the beneficial short-chain fatty acid butyric acid and (ii) diabetic retinopathy by reducing microvascular lesions [ 85 , 86 , 87 ] and reducing the pathogenic factor succinate [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“… Cardiorenal benefits of Sodium–Glucose Cotransporter 2 (SGLT2) inhibitors and proposed effects on SGLT1 activity: Sodium–Glucose Cotransporter 2, SGLT2; Sodium–Glucose Cotransporter 1, SGLT1; Empagliflozin, EMPA; Dapagliflozin, DAPA; Canagliflozin, CANA; CV, cardiovascular; HF, heart failure and MI, myocardial infarction. SGLT1/2 Inhibition: [ 83 , 97 ], SGLT1 Activity: [ 85 , 90 ], Cardio-Renal Protection: [ 25 , 27 , 51 , 54 , 96 ]. Red arrows indicate an increase in the parameter.…”
Section: Figurementioning
confidence: 99%
“…At a molecular level also, it has been recently revealed that Empagliflozin reduced retinal vascular lesions in both Kimba and Akimba mice and Canagliflozin reduced the development of retinal vascular lesions in Kimba mice. 6 It is indeed very insightful to also note that a large retrospective cohort study to assess whether SGLT2-i affected progression of NPDR compared to standard of care concluded that exposure to SGLT2–i therapy was not associated with progression of NPDR compared to patients receiving other standard treatments for T2DM. 7 …”
Section: Sglt2-i and Diabetic Retinopathymentioning
confidence: 99%